Conserved lipid-facing basic residues promote the insertion of the porin OmpC into the E. coli outer membrane - Janine H. Peterson; Lixinhao Yang; James C. Gumbart; Harris D. Bernstein (mBio)
ABSTRACT Almost all integral membrane proteins that reside in the outer membrane (OM) of gram-negative bacteria contain a closed amphipathic β sheet (“β barrel”) that serves as a membrane anchor. The membrane integration of β barrel structures is catalyzed by a highly conserved heterooligomer called the barrel assembly machine (BAM). Although charged residues that are exposed to the lipid bilayer are infrequently found in outer membrane protein β barrels, the β barrels of OmpC/OmpF-type trimeric porins produced by Enterobacterales contain multiple conserved lipid-facing basic residues located near the extracellular side of the OM. Here, we show that these residues are required for the efficient insertion of the Escherichia coli OmpC protein into the OM in vivo. We found that the mutation of multiple basic residues to glutamine or alanine slowed insertion and reduced insertion efficiency. Furthermore, molecular dynamics simulations provided evidence that the basic residues promote the formation of hydrogen bonds and salt bridges with lipopolysaccharide, a unique glycolipid located exclusively in the outer leaflet of the OM. Taken together, our results support a model in which hydrophilic interactions between OmpC and LPS help to anchor the protein in the OM when the local environment is perturbed by BAM during membrane insertion and suggest a surprising role for membrane lipids in the insertion reaction.IMPORTANCEThe assembly (folding and membrane insertion) of bacterial outer membrane proteins (OMPs) is an essential cellular process that is a potential target for novel antibiotics. A heterooligomer called the barrel assembly machine (BAM) plays a major role in catalyzing OMP assembly. Here, we show that a group of highly conserved lipid-facing basic residues in Escherichia coli OmpC, a member of a major family of abundant OMPs known as trimeric porins, is required for the efficient integration of the protein into the outer membrane (OM). Based on our work and previous studies, we propose that the basic residues form interactions with a unique OM lipid (lipopolysaccharide) that promotes the insertion reaction. Our results provide strong evidence that interactions between specific membrane lipids and at least a subset of OMPs are required to supplement the activity of BAM and facilitate the integration of the proteins into the membrane.